Perjanjian Kerjasama Dan Bagi Hasil Antara Pokdarwis Dengan Pemerintah Desa: Studi Di Desa Bilebante, Kecamatan Pringgarata, Kabupaten Lombok Tengah) - Zaiyinul Qiram; Diangsa Wagian (Fakultas Hukum Universitas Mataram, 2023)
This study aims to find out and explain about the cooperation agreement and profit sharing between Pokdarwis and the Bilebante Village Government which is regulated based on Perdes No. 3 of 2016 concerning the Management of Green Tourism Villages in regulating the rights and obligations of both parties and implementation in the field. The research method in this paper is empirical. The results of this study are the rights and obligations of both parties have been regulated in the Village Regulation, for profit sharing according to the agreement of both parties. The implementation carried out in the Village Regulation includes the allocation of funds, the party entitled to manage the Green Tourism Village, and profit sharing for both parties